Editorial de la revista número 2 del año 2018 - Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2018)
The University Institute of the Hospital Italiano has initiated a curricular change that began with the Medicine degree program. Within the context of the Specialization Course in University Teaching for Health Professionals at IUHI, Luis A. Boccalatte describes the change in pedagogical strategies in a Letter to the Editor.In a Brief Communication, Carlos Capiel, from the Diagnostic Imaging Service of the Radiological Institute of Mar del Plata, retrospectively evaluated seven patients with a diagnosis of suprascapular nerve entrapment due to supraglenoid cyst using magnetic resonance imaging.Nanci Giraudo and Valeria Vietto, from the Family and Community Medicine Service, conducted a qualitative study aimed at understanding the experiences reported by individuals with type 2 diabetes attending a primary care center in Greater Buenos Aires.Emma Abalos, from the Artemides Zatti Higher Institute of Nursing, Valeria Vietto, from the Family and Community Medicine Service, and Virginia Garrote, from the Central Library, investigated the composition of the healthcare team and the health care provided to the Army of the Andes under the command of General José de San Martín.The family physician has a holistic view of the family as a whole. Mercedes Mutchinick and Diego Terceiro, from the Family and Community Medicine Service, report a clinical case and the implementation of the FOCO interview (family, orientation, and context) to address the psychosocial and contextual aspects of the family.Based on the description of a clinical case of superinfected facial ulcers, Gabriela Brana and collaborators, from the Dermatology Service, review the diagnostic and therapeutic challenges posed by self-inflicted dermatoses in the context of complex psychiatric disorders.In the “Ask the Expert” section, Alejandro Carbone Zárate, from the Adult Emergency Center, reviews the indication for routine prostate-specific antigen testing in men over 50 years of age.In the “Hospital Italiano in Medline” section, Enrique P. Ubertazzi, from the Gynecology Service, analyzes published results on pelvic organ prolapse surgery using transvaginal synthetic meshes.